2006
DOI: 10.1038/sj.bjc.6603252
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype distribution and cervical squamous intraepithelial lesions among high-risk women with and without HIV-1 infection in Burkina Faso

Abstract: Human papillomavirus (HPV) infection and cervical squamous intraepithelial lesions (SILs) were studied in 379 high-risk women. Human papillomavirus DNA was detected in 238 of 360 (66.1%) of the beta-globin-positive cervical samples, and 467 HPV isolates belonging to 35 types were identified. Multiple (2 -7 types) HPV infections were observed in 52.9% of HPV-infected women. The most prevalent HPV types were HPV-52 (14.7%), HPV-35 (9.4%), HPV-58 (9.4%), HPV-51 (8.6%), HPV-16 (7.8%), HPV-31 (7.5%), HPV-53 (6.7%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
103
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 57 publications
26
103
3
6
Order By: Relevance
“…This finding has implications in the eventual implementation of prophylactic HPV vaccines based on HR-HPV types 16 and 18 (Steinbrook, 2006). Our results add to those reported in a recent meta-analysis of HPV types among HIVinfected women (Clifford et al, 2006) and the recent international data which indicate the increased preponderance of HPV types other than 16 or 18 among HIV-infected women (Levi et al, 2002;Bollen et al, 2006;Didelot-Rousseau et al, 2006;Luque et al, 2006). If cross-reacting immunity is not induced across viral types by existing vaccines, this will limit their efficacy in immunosuppressed women in developing countries whose dominant HR-HPV types may be other than 16 and 18.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This finding has implications in the eventual implementation of prophylactic HPV vaccines based on HR-HPV types 16 and 18 (Steinbrook, 2006). Our results add to those reported in a recent meta-analysis of HPV types among HIVinfected women (Clifford et al, 2006) and the recent international data which indicate the increased preponderance of HPV types other than 16 or 18 among HIV-infected women (Levi et al, 2002;Bollen et al, 2006;Didelot-Rousseau et al, 2006;Luque et al, 2006). If cross-reacting immunity is not induced across viral types by existing vaccines, this will limit their efficacy in immunosuppressed women in developing countries whose dominant HR-HPV types may be other than 16 and 18.…”
Section: Discussionsupporting
confidence: 77%
“…Comparable studies using PCR-based detection of HPV in HIV-infected women have reported 12 -79% of study participants with multiple HPV types (Levi et al, 2002;Moscicki et al, 2004;Bollen et al, 2006;Didelot-Rousseau et al, 2006;Hawes et al, 2006;Luque et al, 2006). This high prevalence may reflect the immune impairment by HIV that fails to clear HPV, leading to chronic HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…24 A prevalence of 66.1% was reported in a study carried out in Burkina-Faso. 25 Similar studies also carried out in other parts of Africa showed a prevalence of as high as 97.2%. 26 These variations in figures may be attributable to the exhaustive nature of the HPV detection strategy used in the various studies especially those carried out in Asia and America.…”
Section: Discussionsupporting
confidence: 58%
“…10 The high HIV prevalence could explain the observed HPV genotype distribution, since HIV-infected women are reported to acquire a broader spectrum of HPV genotypes other than HPV 16 or 18. [11][12][13] Most previous studies in South Africa were conducted in low HIV prevalence areas. This finding is epidemiologically important because the existing vaccine may not be as efficacious in this region of South Africa.…”
Section: Discussionmentioning
confidence: 99%